An arithmetic sequence is a string of numbers that is produced by repeatedly applying a certain arithmetic operation, in this case the string of numbers [tex]t_{1} , t_{2}, t_{3}, ..., t_{n}, ...[/tex] is thus determined, the first term [tex]t_{1}[/tex] is equivalent to number 23 and each next term, [tex]t_{n}[/tex] with [tex]n>1[/tex] (i.e. [tex]t_{2} , t_{3}, t_{4}, ...[/tex]) is calculated using the given formula [tex]t_{n}= t_{n-1} -3[/tex], so the next term in the sequence, [tex]t_{2}[/tex] will be:
[tex]t_{2}= t_{1}-3\\ t_{2}= 23-3 = 20[/tex]
in the same way the following terms are calculated
[tex]t_{3} = t_{2}-3\\t_{3} = 20-3 = 17\\t_{4} = t_{3}-3\\t_{4} = 17-3 = 14\\...\\t_{9} = t_{8}-3\\t_{9} = 2-3 = -1\\t_{10} = t_{9}-3\\t_{10} = -1-3 = -4[/tex]
Another way to achieve this is to use the formula to calculate the terms [tex]t_{n}[/tex], note that:
[tex]t_{2} = t_{1}-3\\t_{3} = t_{2}-3 = (t_{1}-3) -3 = t_{1}-6\\t_{4} = t_{3}-3 = (t_{1}-6) -3 = t_{1}-9=t_{1}-3(3)\\t_{5} = t_{4}-3 = (t_{1}-9) -3 = t_{1}-12=t_{1}-3(4)[/tex]
So, as you see each tn becomes [tex]t_{1}[/tex] minus a multiple of -3, or what is the same:
[tex]t_{n}= t_{1} -3 (n-1)\\t_{n}= 23-3 (n-1)[/tex]
Replacing the desired value
[tex]23-3 (n-1)=-4\\23 + 4 = 3 (n-1)\\27 = 3 (n-1)\\27/3 = (n-1)9 = n-1\\n = 10[/tex]
Answer
the value of n when [tex]t_{n} =-4[/tex] is [tex]n=10[/tex], [tex]t_{10}[/tex]